2019
DOI: 10.3389/fpls.2019.00240
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Embryogenesis Induction in Woody Species: The Future After OMICs Data Assessment

Abstract: Very early somatic embryogenesis has been recognized as a powerful method to propagate plants in vitro . For some woody species and in particular for some coniferous trees, somatic embryogenesis induction has become a routine procedure. For the majority, the application of this technology presents yet many limitations especially due to the genotype, the induction conditions, the number of embryos produced, maturation, and conversion, among other factors that compromise the systematic use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 202 publications
(261 reference statements)
1
21
0
1
Order By: Relevance
“…Several biochemical and genetic studies of SE have been reported, involving A. thaliana [ 43 ], Brassica napus [ 44 ], Medicago truncatula [ 45 ], Coffea spp. [ 2 , 46 ], and many other species [ 4 , 47 , 48 ]. However, the mechanism by which somatic cells change their genetic program and become somatic embryos is not yet fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Several biochemical and genetic studies of SE have been reported, involving A. thaliana [ 43 ], Brassica napus [ 44 ], Medicago truncatula [ 45 ], Coffea spp. [ 2 , 46 ], and many other species [ 4 , 47 , 48 ]. However, the mechanism by which somatic cells change their genetic program and become somatic embryos is not yet fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…The statistical approach employed in this study helped to clearly divide the SE process into five phases and four key phase switches that are strategic for the whole biological efficiency of embryo redifferentiation. Many authors recently reported the necessity of a better understanding of the SE process to clarify the current bottlenecks [22,26,41]. The fact that each of the metabolic profiles correlated with a specific cell status—leaf cells, cells in dedifferentiation, callus cells, pro-embryogenic masses, embryonic cells—is extremely relevant.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, the latest omics technologies (genomics, transcriptomics, proteomics, epigenomics, metabolomics and phenomics) are gaining increasing attention. Many authors believe that combining omics technologies with the in vitro process can have a tremendous impact on the knowledge of the molecular mechanisms underlying SE [22,25,26]. Metabolomics data can provide a wealth of information in the description and elucidation of physiological responses to environmental conditions in plants [27].…”
Section: Introductionmentioning
confidence: 99%
“…SE is considered a very powerful tool in plant biotechnology, as a feasible in vitro procedure for plant cloning and regeneration purposes [ 64 ]. Due to its great potential for large-scale clonal propagation and the cryopreservation of elite genotypes, as well as for production of genetically modified plants with improved traits, SE has been proven to be very useful for propagation of species with long reproductive cycles or low seed set in a large variety of crop and forest species [ 64 , 68 , 69 , 70 ]. In the case of microspore embryogenesis, the microspore (haploid cell, precursor of pollen grain) is reprogrammed towards an embryogenic pathway, by stress treatment [ 71 ].…”
Section: Somatic Embryogenesis: Stress Auxin and Epigenetic Modifmentioning
confidence: 99%